Manuscript verse collectors and the politics of anti-courtly love poetry - Eckhardt, Joshua (Oxford University Press, 2009)
This is an analyis of the contribution to literary history of early 17th century hand-written English poetry anthologies. Compiled by manuscript verse collectors, these anthologies preserved a number of pieces by major authors of the English Renaissance, yet they tended to surround them with unprintable verses on sex and politics.